PENGARUH RASIO KEUANGAN UKURAN PERUSAHAAN DAN TOTAL ASET TERHADAP NILAI PERUSAHAAN DENGAN RETURN SAHAM SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN TEKNOLOGI DI BEI PERIODE TAHUN 2016 - 2020 - Arifin, Alif Rahman; Hamdun, Edy Kusnadi; Sari, Rini Kartika (Fakultas Ekonomi dan Bisnis, 2024)
Technology companies are companies focusing on the field of manufacturing, support,research and at development technology,ComputingAndelektronika. Technology companies are generally engaged in the field ofsoftware,hardware,Renewable Energy, and Internet-based services such ascloud computingande-commerce. This experimental test is to determine the effect of financial ratios, company size and total assets on the value of the company with stock return as an intervening variable. This study uses quantitative and descriptive research. The population used in this study is 96 technology companies listed on the IDX for the 2016-2020 period. The sampling technique in this study uses the purposive sampling. Data analysis and hypothesis testing in this study used Smart PLS 3.0. The results of the direct influence test using the Smart PLS 3.0 application, show that financial ratios have a negative but not significant effect on stock returns, Company size has a positive but insignificant effect on stock returns, Total assets have a positive but insignificant effect on stock returns, Financial ratios have a positive but not significant effect on company value, Company size has a positive but not significant effect on stock returns Company value, Total assets have a positive but insignificant effect on company value, Stock return has a positive but significant effect on company value, Financial ratios have a negative but insignificant effect on company value through stock return, Company size has a positive but insignificant effect on company value through share return, Total assets have a positive but insignificant effect on company value through share return.